An Analysis of Production, Properties & Advantages of Biodiesel (International Journal of Innovative Research in Computer Science & Technology, 2022)
Incessant usage of fossil fuel (non renewable natural resources) is rapidly diminishing, & ir  combustion is causing intensification in carbon dioxide in atmosphere. For ecological & economical sustainability,  renewable carbon-neutral transportation fuels are needed.  Biodiesel made from oil crops has potential to be a carbon neutral sustainable substitute to petroleum-based fuels. It’s  mainly generated via direct usage & mixing, micro emulsions, rmal cracking (pyrolysis), & transesterification,  & is fabricated of mono alkyl esters of long-chain fatty  acids. Transesterification of vegetationoils & animal fats is  most prevalent technique for producing biodiesel. Batch  procedures, supercritical processes, ultrasonic techniques,  & microwave methods are all accessible for trans esterification reaction. Liquid content of oils or fats & free  fatty acids, reaction duration, & reaction temperature are  all variables that affect transesterification process.  significance, history, characteristics, suppliers, & methods  for producing biodiesel are discussed in this study.
Keywords: Atmosphere; Biodiesel; Fossil Fuels; Oil; Petroleum